2018
DOI: 10.1021/acs.jpclett.8b01520
|View full text |Cite
|
Sign up to set email alerts
|

Individual Pathways in the Formation of Magic-Size Clusters and Conventional Quantum Dots

Abstract: The formation relationship between colloidal magic-size clusters (MSCs) and conventional quantum dots (QDs) has not been well established. Here, we report our systematic study on their formation pathways, using cadmium sulfide (CdS) as a model system. Two Cd precursors were prepared from CdO with branched 2-methyloctadecanoic acid (CHCH(CH)-COOH) and linear oleic acid (CHCH-COOH), reacting with elemental S powder in 1-octadecene (ODE). We show that the presence of MSC-311 (exhibiting a sharp absorption peaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
225
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 71 publications
(248 citation statements)
references
References 32 publications
21
225
1
1
Order By: Relevance
“…By a side note, the reactivity of Cd(OA) 2 is higher than that of Cd(MA) 2 , and the PC produced from a Cd(OA) 2 + S reaction batch at 180 C (with a growth period of 15 min) seemed to be more than that from a Cd(MA) 2 + S reaction batch at 200 C (with the same growth period of 15 min). 1 In conclusion, we have demonstrated that it is possible to tune the pathways proposed in the two-step model for the prenucleation stage of colloidal semiconductor ME QDs. 1 Meanwhile, the PC to MSC-311 transformation is also facilitated under such temperatures without a second-step incubation at a lower temperature, which is required for the two-step approach reported.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…By a side note, the reactivity of Cd(OA) 2 is higher than that of Cd(MA) 2 , and the PC produced from a Cd(OA) 2 + S reaction batch at 180 C (with a growth period of 15 min) seemed to be more than that from a Cd(MA) 2 + S reaction batch at 200 C (with the same growth period of 15 min). 1 In conclusion, we have demonstrated that it is possible to tune the pathways proposed in the two-step model for the prenucleation stage of colloidal semiconductor ME QDs. 1 Meanwhile, the PC to MSC-311 transformation is also facilitated under such temperatures without a second-step incubation at a lower temperature, which is required for the two-step approach reported.…”
mentioning
confidence: 78%
“…1 In conclusion, we have demonstrated that it is possible to tune the pathways proposed in the two-step model for the prenucleation stage of colloidal semiconductor ME QDs. 1 Meanwhile, the PC to MSC-311 transformation is also facilitated under such temperatures without a second-step incubation at a lower temperature, which is required for the two-step approach reported. 5 The combined use of a secondary phosphine and an methyl carboxylic acid results in a significant overlap in the temperature range required for the PC formation (Step 1) as well as for the PC to MSC transformation (Step 2), making a one-step approach to single-ensemble MSC production possible.…”
mentioning
confidence: 78%
See 3 more Smart Citations